Implementation of Game Based Learning in Supporting Students' Concept Understanding at SMP Muhammadiyah 18 Surabaya - Sabilie, Akmal; Arifin, Shokhibul; Hidayat, Moch. Charis (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
In this digital era, students generally like fun and creative things. The use of games as a learning tool not only improves conceptual understanding but also strengthens practical skills needed in the real world. In this context, GBL encourages students to learn through experimentation, reflection, and active interaction with the subject matter. This study examines the application of Game-Based Learning (GBL) to improve students' conceptual understanding at SMP Muhammadiyah 18 Surabaya. Using a qualitative method based on case studies, this study identified the impact of GBL on learning outcomes through observation, interviews with teachers and students, and documentation analysis. The results showed that GBL significantly increased students' motivation, participation, and conceptual understanding. In implementation, the use of platforms such as Kahoot facilitates an interactive and fun learning process. Challenges faced include limited resources and the need for teacher training to integrate GBL effectively. Thus, GBL is proven to be an innovative approach that not only strengthens students' cognitive skills but also develops social and collaborative abilities. This study provides insight into the potential of GBL in improving the quality of education through technology-based learning.